الاستلزام الحواري في رائية أبي فراس الحمداني مقاربة بلاغية في ضوء النظرية التداولية - ساسي, ذهبي, لزهاري عبد القادر (Univercty of Eloued, 2020)
التداكلية عمـ جديد لمتكاصؿ الإنساني، يدرس الظكاىر المغكية ٌ في حيز الاستعماؿ المغكم، كمف ىنا جاء تسميتيا بعمـ الاستعماؿ المغكم، الذم يدرس علاقة النشاط المغكم بمستعمميو، كطرؽ ككيفية استخداـ العلاقات المغكية ضمف سياقات كمقامات مختمفة، كما تبحث عف العكامؿ التي تجعؿ مف الخطاب رسالة كاضحة المعالـ. كتعالج التداكلية ٌ عدة مكضكعات ليا صمة كثيقة بتحميؿ الخطابات كالنصكص، ٌ لعؿ مف أبرزىا ذكار "الاستمازـ ٌ كيعد ىذا الأخير مف أبرز المفاىيـ كالظكاىر المنبثقة عف الدرس التداكلي الحديث، ،"الحكارم حيث تبمكر عمى يد الفيمسكؼ "غاريس"، الذم اعتبر أ ٌ ف جمؿ المغة ٌ تدؿ في أغمبيا عمى معاف صريحة ك أخرل ضمنية ٌ تتحدد دلالاتيا انطلاقا مف السياؽ الذم كردت فيو، كما اقترح مبدأ التعاكف كقكاعده الأربعة :"الكـ"، "الكيؼ"، "الطريقة"، ك"الملائمة ٌ كأف ،" ٌ أم خرؽ ليذه القكاعد يؤدم إلى انتقاؿ معنى الجممة الظاىر كالمباشر (الصريح) إ ٌ لى معنى خفي غير مباشر ٌ (مستمزـ )يستدؿ ٌ عميو مف خلاؿ السياؽ .كيشكؿ خطاب القصيدة (ارئية أبي فارس الحمداني)، أم: ىذا الخطاب الشعرم - مف قيـ ك – أرضية خصبة لمدارسات التداكلية لما فيو أبعاد لغكية كسياقية ٌ ميمة ٌ فيك يحمؿ بيف طياتو الكثير مف الدلالات كالمعاني الضمنية المستمزمة ، ،) المتكارية تحت حجاب المعاني الظاىرة كالمباشرة (الصريحة ٌ كالتي تـ التقاطيا كمعانقة فحكل ٌ مقاصدىا مف خلاؿ رككب مطيتي السياؽ كحسف التأكيؿ، لذلؾ كاف مكضكع بحثنا مكسكما بػػػػػ: "الاستمازـ الحكارم في قصيدة أبي فارس الحمداني مقاربة بلاغية في ضكء النظرية التداكلية ٌ كقد ضـ مقدمة، كمدخلا نظريا، كفصميف، كخاتمة، ذكرنا في المقدمة أسباب اختيار ،" المكضكع، شكالية كا ٌ كما يتضمنو مف فصكؿ، ك ،البحث أ ٌ ىـ المصادر كالمارجع، كما تناكلنا في المدخؿ تعريؼ التداكلية ٌ بشقيو المغكم كالاصطلاحي، مع التعريج إلى نشأتيا ك أىدافيا كعلاقتيا بالعمكـ الأخرل، كختمناه ٌ كخصصنا الفصؿ الأكؿ لدارسة ، بالحديث عف مكضكعاتيا ماىية الاستمازـ الحكارم كطبيعتو في الثقافتيف الغربية كالعربية ٌ كتـ تقسيمو إلى ثلاثة أقساـ ، ىي : مفيكـ الاستمازـ الحكارم، تحديد طبيعة الاستمازـ الحكارم في الفكر الغربي مف حيث نشأتو، أنكاعو، كبياف خصائصو، ككذا تسميط الضكء عمى مبدأ التعاكف كقكاعده المتفرعة عنو، كفي نياية ٌ ىذا الفصؿ تـ التطرؽ إلى القكاعد المكممة لمبدأ التعاكف نحك: قاعدة التأدب ، ، ك صديؽ كفي القسـ الثالث كالأخير ٌ ككذا الت ، أدب الأقصى ٌكالت ،كاجوٌالت ٌ مف ىذا الفصؿ تـ الحديث عف طبيعة الاستمازـ الحكارم في الفكر العربي، ٌ كقد تـ ٌ التعرض فيو إلى نقطتيف جكىريتيف ىما : ثنائية الخبر كالإنشاء كعلاقتيما بالاستمازـ الحكارم، كثنائية الحقيقة كالمجاز كعلاقتيما أيضا بالاستمازـ الحكارم، أ ٌ ما الفصؿ الثاني فقد كاف تحت عنكاف "إسقاطات الاستمازـ الحكارم عمى ارئية أ ٌ حيث تـ التركيز فيو أكثر عمى الجانب ،" بي فارس الحمداني التطبيقي، باستثناء الصفحات الأكلى منو التي آثرنا فييا أف نتحدث عف حياة الشاعر كالتعريؼ بو، ككذا الحديث عف القصيدة ٌ مع ذكر مناسبتيا كنصيا، ٌ ثـ ٌ سمطنا الضكء بعدىا ٌ عمى تجميات كتمظيارت "الاستمازـ الحكارم" في القصيدة مف خلاؿ الأساليب الإنشائية الكناية، التشبيو )، ، (الاستفياـ، الأمر، النيي ...) كالخبرية، ككذا الصكر البيانية (الاستعارة كفي القسـ الأ ٌ خير مف ىذا الفصؿ تـ الحديث عف أبرز ٌ الانتياكات التي مست "مبدأ التعاكف" الملائمة"، ك " ،" في القصيدة، عمى غارر قاعدة "الكيؼ" "الطريقة أنيينا ىذا البحث بخاتمة Pragmatics is a new science for human communication, it studies linguistic phenomena in the field of linguistic use, therefore it named science of linguistic use, which studies the relationship of linguistic activity to its users, and methods and how to use linguistic relationships in different contexts, and research the factors that make speech a clear message. The deliberative questions deal with several subjects closely related to the analysis of speeches and texts, the most important of which perhaps mention is «Conversational implicature». It considered one of the most prominent meanings, that determined from the recent pragmatics lesson in which it founded, as suggested by philosopher Grice Which considered that the sentences of the language mostly indicate explicit and implicit meanings whose significance is determined from the context in which it is received, He also proposed the principle of cooperation and its four rules: “Quantity”, “Quality”, “Method”, And that any breach of these rules leads to the transfer of the apparent and direct (explicit) meaning of the sentence to an indirect hidden meaning (required) that is evidenced by the context. The speech of the poem (Raya Abi Firas Al-Hamdani) is a fertile ground for deliberative studies of what it contains - that is: this poetic discourse - of important linguistic and contextual values and dimensions, as it carries many of the implications and implied meanings hidden under the veil of apparent and direct (explicit) meanings, which was understood the meaning and the intent of its intentions by overlapping context and good interpretation, so that the subject of our research which untitled: "The Conversational implicature in the poem of Abi Firas AlHamdani is a rhetorical approach in the light of pragmatics theory." It included an introduction, a theoretical introduction, two chapters and a conclusion, mentioned in Introduction The reasons for the choice of the subject, the problematic and what it contains chapters, and the most important sources and references, such as we discussed in the entry the definition of the pragmatics, linguistic and idiomatic, definition with the definition of its origins and objectives and its relation with the other sciences, and we concluded it by its subjects, and we devoted the first chapter to study what is the implicature of conversation and its nature in Western and Arab cultures were divided into three sections: the concept of implicature of conversation, and its nature in Western thought in terms of its origins, types and its characteristics, as well as to shed light on the principle of cooperation and its ensuing rules, and at the end of this Chapter, the rules which complement the principle of cooperation towards: the rule of politeness, confrontation, extreme politeness and ratification, and in the third last section in this chapter, we talk about the nature of implicature conversation in western thought, that include two initials points: the duality of comment and….their relation to the implicature conversation. As for the second chapter, it was untitled the title “Projections of the implicature conversation on the vision of Abi Firas Al-Hamdani”, where the emphasis was placed more on the applied side with the exception of the first pages, in which we preferred to talk about the life of the poet and his biography, as well as the poem by mentioning its occasion and its text, we then highlight the manifestations of the " implicature conversation " in the poem by constructive methods (interrogation, imperative, ban. Etc.) And Informative, as well as graphic images (metaphor, simile, metonymy) and in the last section of this chapter we talk about the most important violations that have affected the " principle of cooperation "in the poem, along the lines of the rule" How "," the way "," appropriate ", and we ended this search with a conclusion that contained the results of the search.
Keywords: التداولية الاستلزام الحواريالخطاب الشعري السياق الاساليب الانشائية الاساليب الخبرية; pragmatics, conversation implicature, context, poetic discourse, literal (explicit) meaning, implicit (implicit) meaning, structural methods, current styles, graphic images. The poem, Abu Firas al-Hamdani